White Grubs, Phyllophaga spp. (Insecta: Coleoptera: Scarabaeidae) - H.L. Selman (EDIS)
This document provides an in-depth profile of white grubs, specifically the larvae of May beetles in the genus Phyllophaga. It covers their distribution, physical description, life cycle, and management strategies. White grubs are significant agricultural pests, causing damage to crops by feeding on plant roots. The article discusses various control methods, including cultural practices, natural enemies, and biological control agents. It also highlights the importance of timely plowing and planting strategies to mitigate grub infestations. Original publication date July 1998.